Does CSR Create Value for Companies In Malaysia? An Empirical Study of Effect of CSR towards Financial Performance on Shariah and Non Shariah-Compliant Companies in Malaysia - Ding, Huey Chyi (2015)
Over the years, there has been a significant rise in the awareness and practice of Corporate Social Responsibility (CSR) globally. Studies covered various dimensions of CSR have been carried out extensively in developed countries, with results varied that CSR active companies outperformed their peers in term of financial returns, others shown no significant correlations while some concluded that CSR activities do not pay. Similar trend of research gained distinctive attention from the developing countries in last decade, particularly in assessing the frameworks, factors and influence of CSR activities towards financial performances and investment returns; whilst others focus on gauging the extent of CSR contributions over companies’ value creation. This study aims to examine the relationship between CSR and company financial performance in the context of Malaysia. Among the developing countries, Malaysia is avidly promoting and underlying CSR efforts as part of the Government’s blueprint for country’s growth. Positive CSR environment can be seen with both mandatory reporting of CSR for Public Listed companies and incentive policy, including double deduction in the tax computation for CSR activities being extended to 31 December 2020 under 11th Malaysia Plan. Next, having been classified as one of the dominant Global Islamic financial hubs and undisputable largest global issuer of Islamic Bond - sukuk, it would be interesting to create a link between CSR and some measure of Social Responsible Investing (SRI),represented by shariah-compliant companies as Islamic principles emphasized the importance of ethical responsibility that eliminate all harmful actions that might affect the welfare of the community, which is in line with the purpose of CSR. The findings showed that CSR does impact company’s financial performance in Malaysia, albeit the results are insignificant empirically due to limited sample size. However, it is worth noting that shariah-compliant companies with low CSR activities are more inclined to better financial performance. This may be unique in the context of Malaysia given its strong Islamic financial status where Islamic-based equity investment funds stood at RM38.2 billion as at 2014. Overall, the conclusion could be drawn in this paper that positive screening of the companies’ activities in accordance to Shariah principal with certain extent of CSR will create the most value of companies in Malaysia.